Forecasting Equity Market Performance: A Comparative Analysis of Linear Regression, Random Forest, and LSTM Approaches - Dody Suhermawan; Krisna Didit Wiwaha; Muchammad Ilham SAM (PT. Mawadaku Sukses Solusindo, 2025)
This research explores the predictive capabilities of three distinct modeling approaches—Linear Regression, Random Forest, and Long Short-Term Memory (LSTM)—in forecasting stock prices using data from 29 companies, including the S&P 500 index, spanning from January 1, 2000, to June 27, 2024. Through the utilization of historical time-series data, the study evaluates model performance based on key statistical indicators: Mean Squared Error (MSE), Root Mean Squared Error (RMSE), and the coefficient of determination (R²). The findings indicate that while Random Forest outperforms Linear Regression in terms of accuracy, the LSTM model consistently delivers superior results, attributed to its strength in capturing sequential dependencies within financial data. These insights contribute to the growing body of literature in financial analytics by highlighting the comparative strengths of traditional, ensemble-based, and deep learning methods for stock market prediction. Furthermore, the study opens up avenues for integrating advanced temporal models into future financial forecasting frameworks.